GAINS FROM INTERNATIONAL DIVERSIFICATION AND DOMESTIC PORTFOLIO IN EMERGING STOCKS MARKETS: PHILIPPINE AND INDONESIAN PERSPECTIVES - Eduardus Tandelilin (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 1999)
The study was organized into two major concerns: first, identifying the gains from international diversification in emerging stock markets from the Philippine and the Indonesian perspectives and determining which perspective yields the greater gains; and second, determining how many securities must be included to obtain an optimal investment portfolio from the Philippine and Indonesia perspectives.The empirical results indicate that there are gains from international diversification, both from the Philippine and Indonesian perspectives, in two to eight emerging stock markets. Generally the gains are greater from the Indonesian perspective than the Philippine perspective in all countrycombinations.Further, this study found that the number of stocks needed to form an optimum domestic investment portfolio was bigger for the Indonesian investor‘s perspective (at 15 stocks) than for the Filipino investor (14).